2023
DOI: 10.26434/chemrxiv-2022-hfk25-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Consequences of Overfitting the van der Waals Radii of Ions

Abstract: Atomic radii play important role in scientific research. The covalent radii of atoms, ionic radii of ions, and van der Waals (VDW) radii of neutral atoms can all be derived from crystal structures. However, the VDW radii of ions are a challenge to determine because the atomic distances in crystal structures were determined by a combination of the VDW interactions plus the electrostatic interactions, making it unclear how to define the VDW sphere of ions in such an environment. In the present study, we found th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The results from this study 72 show that two histidine residues contributing to the metal coordination sites lose their interactions with the metal ion. Two oxygen atoms from the negatively charged residues in the binding site then take over and coordinate with the metal ion in a bidentate mode.…”
Section: Binding Free Energy and The Chelator Atomsmentioning
confidence: 66%
See 1 more Smart Citation
“…The results from this study 72 show that two histidine residues contributing to the metal coordination sites lose their interactions with the metal ion. Two oxygen atoms from the negatively charged residues in the binding site then take over and coordinate with the metal ion in a bidentate mode.…”
Section: Binding Free Energy and The Chelator Atomsmentioning
confidence: 66%
“…35 A previous study on this protein indicates that the z12−6 parameters fail to maintain the coordination modes of both Ni(II) binding sites after 80 ns of MD simulations. 72 This metalloprotein is a homodimer comprising two metal-binding sites, with each binding site including His5, His74, Glu122, and Glu56 and two water molecules coordinating with one nickel (see Figure 6).…”
Section: Binding Free Energy and The Chelator Atomsmentioning
confidence: 99%
“…249,250 Nevertheless, it remains questionable the generalizability and transferability of nonbonded 12−6 Mg 2+ models to RNA systems. 251 Water molecules also play an important role in nucleic acid dynamics because the hydration patterns around nucleic acids help to stabilize RNA molecules. 159 As such, the water model's choice significantly impacts the conformational ensemble resulting from MD simulations.…”
Section: 130mentioning
confidence: 99%
“…This thorough investigation demonstrated that Li's approach yielded excellent results for a wide range of cations while significantly reducing the computational overhead associated with polarization calculations. 28 Such an approach has already been used for refining previous force fields of mono-atomic cations in interaction with nucleic acids, 29 proteins, 30 and imidazole. 31 It has also been recently used for developing new force fields for actinyl AnO 2 + and AnO 2 2+ cations (An = U, Np, and Pu) .…”
Section: Introductionmentioning
confidence: 99%